STUDI EKSPLORASI POLA KOMUNIKASI PEMBELAJARAN BERBASIS VIRTUAL - Saiful, Anwar; Hasanah, Uswatun; Musa, Musa (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Improvements in communication technology have a broad impact in various fields, including education. The pattern of learning communication has changed from face-to-face learning activities to virtual-based learning. This virtual-based communication pattern is getting stronger with the presence of the Covid-19 pandemic. This research aims to eksplore various articles related to virtual-based learning communication patterns. This research uses the Systematic Literature Review (SLR) method with meta-synthesis analysis techniques. Data collection in this study was carried out by collecting articles from 2020-2023 that have a similar focus. The articles analyzed in this study were 9 accredited national journal articles obtained from the Google Scholar database using Harzing's Publish or Perish application with the keyword virtual-based learning communication patterns. This study found that the virtual learning process can run well, not only supported by mastery of the application used but also supported by the involvement of parents as a substitute for the teacher's role in the learning process as a facilitator, motivator, and director.